The Impact of Local Revenue, Capital Expenditure, Transfer Funds and The Open Unemployment Rate on Local Economic Growth in The Province of West Nusa Tenggara - Saputri, Intan Paraswari; M. Firmansyah; Wafik , Ahmad Zaenal (Journal of Social Growth and Development Studies, 2026)
This study aims to analyse the impact of local revenue (PAD), capital expenditure, transfer funds, and the open unemployment rate (TPT) on the economic growth rate of regencies and cities in West Nusa Tenggara Province for the period 2020–2024. This study employs a quantitative approach using secondary data in the form of panel data obtained from the Central Statistics Agency (BPS). The analysis method used is panel data regression with the aid of the Eviews application; the best model selected is the Fixed Effects Model (FEM). Simultaneously, PAD, capital expenditure, transfer funds, and TPT have a significant effect on the economic growth rate. Partially, PAD and transfer funds have a positive but insignificant effect on the economic growth rate, whilst capital expenditure and TPT have a negative and significant effect on the economic growth rate.